2015
DOI: 10.1016/j.nlm.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Latent memory facilitates relearning through molecular signaling mechanisms that are distinct from original learning

Abstract: A highly conserved feature of memory is that it can exist in a latent, non-expressed state which is revealed during subsequent learning by its ability to significantly facilitate (savings) or inhibit (latent inhibition) subsequent memory formation. Despite the ubiquitous nature of latent memory, the mechanistic nature of the latent memory trace and its ability to influence subsequent learning remains unclear. The model organism Aplysia californica provides the unique opportunity to make strong links between be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Animals were trained with four TSs (120 mA for 1.5 sec, ITI ¼ 10 min), and then the central nervous system chamber, which contains the tail sensory neurons, was exposed to U0126 or U0124 (20 mM) for 3 h. This duration was chosen because it represents the time period during which post-training MAPK activation is sustained in tail SNs (Sharma et al 2003b). Importantly, previous work has shown that U0126 treatment does not disrupt baseline responding as assessed for up to 20 h after treatment (Sharma et al 2003b;Menges et al 2015). After training and drug incubation, the preparations were tested the next day (18-20 h) for LTM.…”
Section: Ltm Requires Mapk Activity During Consolidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were trained with four TSs (120 mA for 1.5 sec, ITI ¼ 10 min), and then the central nervous system chamber, which contains the tail sensory neurons, was exposed to U0126 or U0124 (20 mM) for 3 h. This duration was chosen because it represents the time period during which post-training MAPK activation is sustained in tail SNs (Sharma et al 2003b). Importantly, previous work has shown that U0126 treatment does not disrupt baseline responding as assessed for up to 20 h after treatment (Sharma et al 2003b;Menges et al 2015). After training and drug incubation, the preparations were tested the next day (18-20 h) for LTM.…”
Section: Ltm Requires Mapk Activity During Consolidationmentioning
confidence: 99%
“…Thus, we examined, in turn, whether persistent MAPK activation required translation and transcription. Ring ganglia were preincubated with the general protein synthesis inhibitor emetine (100 mM; Sutton et al 2001;Menges et al 2015) or vehicle (ASW) for 1 h and then trained (four tail-nerve shocks, ITI ¼ 10 min) in the presence of drug. We harvested sensory neuron clusters at either 5 min or 1 h post-training.…”
Section: Sustained But Not Immediate Post-training Mapk Activation mentioning
confidence: 99%
“…Savings is when a memory that seems completely forgotten (via recall tests) can nevertheless be re-acquired more rapidly or easily, indicating that some aspect of the original memory persisted. Savings has been documented across a wide range of learning tasks (Nelson, 1985) and species (Antzoulatos, Wainwright, Cleary, & Byrne, 2006; Menges, Riepe, & Philips, 2015; Philips, Tzvetkova, Marinesco, & Carew, 2006). Similarly, reminders and contextual cues can rescue recall not only from time-dependent forgetting but also from amnestic interventions such as electroconvulsive shock and the disruption of protein synthesis (reviewed in Riccio & Richardson, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…He found that it always took less training to re-learn the lists compared with the original acquisition. Since that pioneering demonstration, savings memory has been demonstrated with multiple learning paradigms ( Nelson, 1985 ) and in a variety of species ( Antzoulatos et al, 2006 ; Philips et al, 2006 ; Menges et al, 2015 ), suggesting that it is a core feature of long-term memory.…”
Section: Introductionmentioning
confidence: 99%